+0  
 
-2
50
1
avatar+199 

f ( x) = 2x2 − 3x + 1 and  g ( x) = 6x2 + 9x + 4

Find the following using the given functions . ( Simplify your answers completely.)

 

  a .  ( f  + g ) (x) = 

 

(b)

( f  + g ) (2) = 

 

(c)

( f  − g ) (x) = 

 

(d)

( f  − g ) (−3) =

 Apr 8, 2020
 #1
avatar+930 
0

a. (f+g)(x)= 2x^2-3x+1+6x^2+9x+4= 8x^2+6x+5

b. (f+g)(2)= 8 * 2^2 + 6 * 2 +5 = 49

c. (f-g)(x)= 2x^2-3x+1-6x^2+9x+4= -4x^2-9x-3

d. (f-g)(-3)= -4 * (-3)^2 - 9 * (-3) - 3= -12

 

Hope it helps!

 Apr 8, 2020

13 Online Users

avatar
avatar